2020
DOI: 10.1136/jclinpath-2019-206092
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression is an unfavourable prognostic indicator in Asian renal cell carcinomas

Abstract: Background/aimsThe programmed cell death receptor 1 (PD-1) checkpoint inhibitor, nivolumab, has been approved for the treatment of metastatic renal cell carcinoma (RCC). However, the understanding of the expression and distribution of PD ligand 1 (PD-L1) in the tumour immune microenvironment and its prognostic role in an Asian cohort is limited. Our group investigated PD-L1 protein expression in a cohort of Asian patients with RCC of mixed ethnicity, using two commercially available antibody clones.MethodsE1L3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…However, the powerful biomarkers are warranted for predicting the drug response of immune checkpoint inhibitors. Previous researchers found that PD-1 or PD-L1 expression levels, MSI status, and mutational load were not ideal factors for predicting the benefits of drugs with lower sensitivity ( 33 35 ). So far, whether TMB correlates with improved survival outcomes or promotion of immunotherapies remains controversial in ccRCC and large cohorts are needed to validate its significance ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the powerful biomarkers are warranted for predicting the drug response of immune checkpoint inhibitors. Previous researchers found that PD-1 or PD-L1 expression levels, MSI status, and mutational load were not ideal factors for predicting the benefits of drugs with lower sensitivity ( 33 35 ). So far, whether TMB correlates with improved survival outcomes or promotion of immunotherapies remains controversial in ccRCC and large cohorts are needed to validate its significance ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clear cell RCC is the most common RCC subtype and has already been extensively analyzed for PD-L1 expression in earlier studies [ 14 , 18 21 , 25 , 26 , 28 , 29 , 31 , 32 , 35 , 39 , 40 , 49 , 51 ]. Our rate of 2–6% PD-L1 positive clear cell RCCs (depending on the cut-off level to define PD-L1 positivity) is in the lower range of published data with PD-L1 positivity ranging from 0 to 77% in studies analyzing 34–756 clear cell RCCs [ 14 , 18 21 , 25 , 26 , 28 , 29 , 31 , 32 , 35 , 39 , 40 , 49 , 51 ]. Reasons that are typically hold accountable for discrepant results in IHC studies include different antibodies, staining protocols, and criteria to define positivity.…”
Section: Discussionmentioning
confidence: 99%
“…1). These studies have described PD-L1 positivity to occur in 0–47% of clear cell RCC at a cut-off level of 1% or 5% stained cancer cells to define positivity [ 18 , 19 , 25 , 28 , 32 , 35 , 49 , 51 ]. The quantity of tissue analyzed per patient and difficulties in the distinction of interspeared PD-L1 positive macrophages that are interspersed between cancer cells from true PD-L1 positive cancer cells might also contribute to the data diversity of PD-L1 immunohistochemistry in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations